Constructivism in Higher Education: Exploring How and Why We Learn at University (Revista de Psicología, 2025)
This essay builds on key themes explored in a graduate seminar and is linked to a doctoral thesis project examining the challenges of university access, retention, and the increasing use of virtual learning. It focuses on the main theoretical developments of constructivism and its connection to the integration of digital technologies in higher education. Constructivism, regarded as one of the most influential theories in psychology and education, posits that knowledge is actively constructed through interaction with the environment. Within this framework, the perspectives of three key theorists are examined: Jean Piaget, Lev Vygotsky, and Jerome Bruner, whose contributions have profoundly shaped our understanding of learning. Piaget emphasized cognitive development through structured stages, while Vygotsky highlighted the role of social interaction and cultural context in the learning process. Bruner, in turn, blended both approaches, advocating for discovery-based learning. The essay critically examines how the integration of digital technologies has reshaped educational dynamics from a constructivist standpoint, particularly in higher education, prompting a reflection on pedagogical methods and how students engage with knowledge in virtual settings. Ultimately, the essay explores both the opportunities and challenges that digital tools present for the active construction of knowledge, offering insights and raising questions that contribute to the ongoing debate about the growing virtualization of higher education from a constructivist perspective.
Keywords: Constructivist paradigm; learning; higher education; interactivity; digital technologies